THE ROLE OF ARTIFICIAL INTELLIGENCE IN LANGUAGE LEARNING: CONTEMPORARY TECHNOLOGIES AND THEIR EDUCATIONAL IMPACT - G‘ulomjonov Shohjahon Rustam o‘g‘li (“SUN’IY INTELLEKTNING TIL O‘RGANISHDAGI O‘RNI” MAVZUSIDA TALABALAR ILMIY-AMALIY KONFERENSIYASI, 2025)
This thesis explores how artificial intelligence technologies can be integrated into language learning settings. By examining recent research and case studies from 2020 to 2024, the study highlights both the benefits and challenges that come with using AI to improve language learning outcomes. The findings indicate that AI tools, such as adaptive learning systems, speech recognition software, and natural language processing applications, present significant opportunities for creating personalized learning experiences. These technologies can offer immediate feedback and address the varied needs of learners effectively. However, for these technologies to be successfully implemented, it is crucial to provide educators with substantial professional development, address equity concerns, and establish strong data privacy measures.This research adds to the ongoing conversation about the role of technology in language education by suggesting a thoughtful framework for the responsible and effective use of AI in teaching contexts.